An ionic liquid-metal organic framework composite material with adjustable confined microenvironment and a preparation method and application thereof
Patent Information
- Application Number
- CN202611028956.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-23
AI Technical Summary
然而,现有离子液体功能化MOFs材料大多采用物理浸渍、表面负载或后修饰接枝等方式引入离子液体,离子液体易聚集于MOFs外表面或孔口位置,存在孔道堵塞、有效孔容下降、传质受限及离子液体流失等问题;此外,现有研究更多关注离子液体作为催化活性中心或表面改性组分,对于如何利用MOFs孔道空间构筑可调控的限域微环境,实现孔道内部界面化学环境、极性分布及配位位点的协同调控,以提高镧系稀土离子的识别能力和选择性分离性能,尚缺乏系统研究
(1)首次实现非聚合/非偶联受限态离子液体在MOFs孔道内的原位构筑与可调限域微环境的精准构建:区别于现有技术中将离子液体聚合成聚离子液体、共价接枝于MOFs骨架、或通过偶联反应放大分子尺寸后封装的技术路径,本发明采用离子液体前驱体在MOFs孔道限域空间内直接原位形成离子液体,使其以非聚合、非偶联、非共价键合的形式,利用孔道限域作用稳定存在于孔道内部。该方式完整保留了离子液体单体的分子构象自由度、配位特性和极性特征,避免了聚合或偶联导致活性位点被屏蔽的问题。在此基础上,本发明首次提出“可调限域微环境”概念,通过调控离子液体的阳离子烷基链长度、阴离子类型及功能基团种类,实现孔道内部极性、电负性、配位能力和亲疏水性的梯度分布,形成具有空间异质性的限域微环境,使MOFs由传统的“多孔吸附材料”转变为具有主动识别能力的“限域微环境识别平台”。
Smart Images

Figure CN122955467A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to metal-organic framework materials and their preparation methods, specifically to an ionic liquid-metal-organic framework composite material with an adjustable confined microenvironment, its preparation method, and its applications. Background Technology
[0002] Rare earth elements, due to their unique electronic structure and excellent magnetic, photocatalytic, and electrocatalytic properties, are widely used in new energy materials, permanent magnet materials, catalysts, electronic information, and defense industries, and are hailed as the "industrial vitamins" of modern industry and an important strategic resource. With the development of high-end manufacturing industries and strategic emerging industries such as new energy vehicles, wind power generation, semiconductors, and high-performance energy storage devices, the demand for high-purity rare earths, especially single rare earth products, continues to grow, placing higher demands on the efficient development and high-purity separation of rare earth resources.
[0003] However, lanthanide rare earth elements share similar electronic structures and chemical properties, primarily existing as trivalent ions in aqueous solutions. Their ionic radii exhibit only minor, regular variations, resulting in remarkably similar coordination behaviors, complexing abilities, and chemical reactivity. Therefore, efficient separation of rare earth elements, especially adjacent lanthanides, has always been a significant scientific and technological challenge in the comprehensive utilization of rare earth resources. Currently, industrial methods for rare earth separation mainly employ solvent extraction, ion exchange, and precipitation. While solvent extraction offers high separation efficiency, it generally suffers from problems such as high organic solvent consumption, long process flows, high acid and alkali consumption, large equipment investment, and environmental pollution. Ion exchange methods have limitations, including limited adsorption capacity, low separation efficiency, and long operating cycles. Therefore, developing novel rare earth separation materials with high selectivity, high adsorption capacity, easy regeneration, and environmental friendliness is of great significance.
[0004] Metal-organic frameworks (MOFs) are a class of crystalline porous materials formed by coordination between metal ions (or metal clusters) and organic ligands. They possess characteristics such as high specific surface area, tunable pore size, designable structure, and high degree of surface functionalization, attracting widespread attention in fields such as gas adsorption and separation, catalysis, drug delivery, and heavy metal ion removal. In recent years, MOFs have been increasingly applied to the adsorption and separation of rare earth metal ions due to their abundant unsaturated metal sites and tunable pore structure. Studies have shown that MOFs can adsorb rare earth ions through pore size sieving, electrostatic interactions, and coordination. However, due to the extremely small size differences among lanthanides, relying solely on the pore size effect of MOFs and the limited number of active sites makes it difficult to effectively distinguish between chemically similar rare earth ions, resulting in limited selective adsorption capacity. Furthermore, some MOF materials exhibit insufficient stability in aqueous solutions, have a limited number of functional sites, and require further improvement in adsorption capacity and cycling stability.
[0005] Ionic liquids (ILs) are a novel class of functional media composed entirely of anions and cations. They possess advantages such as low vapor pressure, good thermal stability, designable structure, and strong coordination ability. By controlling the types of cations and anions and the structure of functional groups in ionic liquids, different Lewis basicities, complexing abilities, and hydrophilic / hydrophobic properties can be imparted to them. Therefore, they are widely used in metal ion extraction and separation, catalytic reactions, and functional adsorption materials. In recent years, the introduction of ionic liquids into MOFs to construct ionic liquid-functionalized MOF composites has been observed, which can, to a certain extent, increase the number of functional sites and interfacial chemical properties of the materials, thereby improving the adsorption performance and stability of MOFs. However, most existing ionic liquid-functionalized MOF materials introduce ionic liquids through physical impregnation, surface loading, or post-modification grafting. Ionic liquids tend to accumulate on the outer surface or pore sites of MOFs, leading to problems such as pore blockage, reduced effective pore volume, limited mass transfer, and ionic liquid loss. Furthermore, current research focuses more on ionic liquids as catalytic active centers or surface modification components. There is a lack of systematic research on how to utilize the pore space of MOFs to construct tunable confined microenvironments and achieve synergistic regulation of the interfacial chemical environment, polarity distribution, and coordination sites within the pores to improve the recognition ability and selective separation performance of lanthanide rare earth ions.
[0006] However, from a technical perspective, current research on ionic liquid-functionalized MOF composites mainly follows these directions: First, after introducing ionic liquids into the pores of MOFs, they are converted into polyionic liquids or ionic liquid polymers through polymerization. While this method can improve the stability of functional components to some extent, the polymerization reaction fundamentally alters the molecular size, spatial configuration, and distribution of active sites of the ionic liquid. The original molecular recognition ability and coordination characteristics of the ionic liquid monomers are significantly weakened, and the introduction of polymers often severely reduces the effective pore size and specific surface area of MOFs pores, leading to a decrease in mass transfer efficiency. Second, functionalized ionic liquids are introduced through covalent bonding. Grafting or anchoring to the MOF framework or organic ligands can achieve stable immobilization of ionic liquids, but covalent bonding restricts the conformational freedom and spatial orientation of the ionic liquids, making it difficult to form a continuous and tunable polar distribution and coordination microenvironment within the porous structure. Furthermore, the grafting process usually involves complex chemical synthesis steps, which may affect the integrity and order of the MOF framework. Thirdly, polymerization or coupling methods can be used to encapsulate ionic liquids into MOF cages after molecular size expansion. Although this method achieves physical confinement, the encapsulated guest molecules are ionic liquid derivatives rather than the ionic liquid itself, and their physicochemical properties are significantly different from the original ionic liquid.
[0007] Furthermore, existing research focuses more on ionic liquids as catalytic active centers or functional components for gas adsorption. Systematic studies have yet to explore how to utilize the confinement effect of MOF nanopores to construct tunable confined microenvironments with polar gradients or spatial heterogeneity by controlling the spatial distribution and aggregation state of ionic liquids within the pores. This would enable highly efficient and selective separation of lanthanide rare earth ions, especially heavy rare earth elements with very similar chemical properties, in liquid-phase systems. The identification and separation of lanthanide rare earth ions still primarily rely on the pore size sieving effect of MOFs themselves and the coordination effect of framework active sites, making it difficult to effectively distinguish adjacent lanthanide elements with minimal differences in ionic radius.
[0008] Therefore, developing a novel ionic liquid-metal-organic framework composite material capable of constructing a stable and tunable confined microenvironment within the pores of MOFs, and achieving synergistic regulation of the ionic liquid and the pore structure and interfacial interactions of MOFs, while maintaining the high porosity and good mass transfer performance of MOFs, can improve the material's selective recognition ability, adsorption capacity, and cycle stability for lanthanide rare earth ions. This has significant theoretical and engineering application value for achieving efficient, green, and low-energy-consumption rare earth resource separation and recovery. Summary of the Invention
[0009] To achieve the above objectives, this invention proposes an ionic liquid-metal-organic framework composite material (IL@MOFs) with a tunable confined microenvironment, its preparation method, and its applications. By directly constructing a non-polymerized, non-coupled, and non-covalently bonded confined ionic liquid in situ within the pores of metal-organic framework (MOFs), and utilizing the spatial confinement effect of the MOF nanopores to achieve stable confined encapsulation of the ionic liquid within the pores, a confined microenvironment with tunable polarity, tunable coordination ability, and tunable hydrophilicity / hydrophobicity is constructed. Unlike existing technologies that polymerize ionic liquids (polyionic liquids), covalently graft them onto the framework, or encapsulate them after scaling up the molecular size through coupling reactions, this invention uses an ionic liquid precursor to form the ionic liquid in situ within the confined space of the MOF pores. This allows the ionic liquid to exist stably in a confined state within the pores, and achieves uniform and spatially coordinated distribution of functional sites within the pores through one or more non-covalent interfacial interactions, such as electrostatic interactions, hydrogen bonding, and van der Waals interactions, between the ionic liquid and the MOF framework. By controlling the types of cations, anions, functional groups, and their spatial distribution and aggregation state within the pores of the ionic liquid, this invention enables the synergistic control of polarity gradient distribution, coordination ability gradient distribution, and hydrophilicity / hydrophobicity gradient distribution within the pores of MOFs, forming a tunable confined microenvironment with spatial heterogeneity. This transforms the traditional "porous adsorption material" into a "confined microenvironment recognition platform" with active recognition capabilities. This tunable confined microenvironment, targeting the similar radii and chemical properties of lanthanide rare earth ions, enhances the adsorption energy differences between different rare earth ions through differentiated recognition of rare earth ions in different regions within the pores, thereby achieving highly selective adsorption and efficient separation of lanthanide rare earth ions. Simultaneously, because the ionic liquid is confined within the pores in a non-covalent form without disrupting the crystal structure of the MOFs, the composite material exhibits excellent pore structure stability and low ionic liquid loss rate in the liquid phase system, endowing the material with good recyclability. Through the above technical solution, this invention achieves an adsorption capacity of ≥50 mg / g for lanthanide rare earth ions and Lu... 3+ / Yb 3+ With a separation coefficient ≥1.5 and an adsorption capacity retention rate ≥80% after 5 cycles, the technology provides a novel material solution for the efficient, green, and low-energy separation and recycling of rare earth resources.
[0010] Terminology Explanation: In this invention, the term "in-situ construction" refers to the process of introducing an ionic liquid precursor into the channels of pre-synthesized activated MOFs, directly forming the ionic liquid within the confined space of the MOF channels through chemical reactions or physical self-assembly, and stably encapsulating the ionic liquid within the channels by utilizing the spatial confinement effect of the MOF nanopores. This differs from methods that load pre-synthesized ionic liquids onto the surface or channels of MOFs through physical adsorption or impregnation, as well as template methods that introduce ionic liquids as template agents during MOF synthesis and subsequently remove them, and polyionic liquid methods that pre-polymerize ionic liquid monomers before introducing them into the MOF channels.
[0011] The term "tunable confined microenvironment" refers to a spatially heterogeneous microenvironment within the nanopores of MOFs, characterized by gradient variations in polarity, electronegativity, coordination ability, and hydrophilicity / hydrophobicity, formed from the inner wall to the center of the pores by controlling the types of cations, anions, functional groups, and their spatial distribution of the ionic liquid confined within the pores. The function of this microenvironment can be directionally controlled by altering the composition and distribution of the ionic liquid, thereby enabling differentiated recognition of different lanthanide rare earth ions. This differs from the pore size sieving effect of MOFs themselves or the single coordination environment provided by unsaturated metal sites, and also from the random aggregation state of the ionic liquid formed within the pores by physical impregnation methods.
[0012] The term "non-polymerized, non-coupled, and non-covalently bonded free state" refers to the existence of ionic liquids within the pores of MOFs as independent anions, cations, or ion pairs. Their molecules do not form polymer chains or cross-linked networks through polymerization reactions, nor do they form covalently linked dimers or polymers through coupling reactions, nor are they anchored to the MOF framework by covalent chemical bonds. Instead, they exist stably within the pores through intermolecular interactions such as electrostatic interactions, hydrogen bonding, and van der Waals interactions. In other words, the ionic liquid in this invention exists simultaneously in a "confined state" and a "free state"—it is physically confined by the MOF pores and cannot freely escape (confined), but it does not form chemical bonds with the framework (free / non-covalent). The coexistence of these two states constitutes the core feature of this invention.
[0013] According to a first aspect of the present invention, an ionic liquid-metal-organic framework composite material with an tunable confined microenvironment is provided, wherein: The composite material comprises metal-organic frameworks (MOFs) and an ionic liquid confined within the pores of the MOFs. The ionic liquid exists stably inside the MOFs channels in a confined state that is non-polymerized, non-coupled, and non-covalently grafted through in-situ construction. It exists stably through the confinement effect of the channels and forms one or more interfacial interactions with the MOFs framework, including electrostatic interactions, hydrogen bonding interactions, and van der Waals interactions. The introduction of the ionic liquid does not destroy the crystal structure of the MOFs. The ionic liquid forms a tunable confined microenvironment within the MOF pores. This tunable confined microenvironment is achieved by controlling the composition of the ionic liquid, the type of functional groups, and their spatial distribution within the pores, thereby synergistically regulating the polarity, electronegativity, coordination ability, and hydrophilicity / hydrophobicity within the pores. The ionic liquid exhibits a gradient polarity distribution or a synergistic distribution of multifunctional sites within the pores, forming a confined microenvironment with spatial heterogeneity. The composite material exhibits selective adsorption and separation properties for lanthanide rare earth metal ions, and maintains structural stability and adsorption performance during recycling.
[0014] Furthermore, the metal center of the MOFs is selected from one or more of Zn, Cu, Zr, Fe, Al, and Cr; the organic ligand of the MOFs is selected from one or more of carboxylic acid ligands, imidazole ligands, pyridine ligands and their derivatives.
[0015] Preferably, the MOFs are selected from one or more of the UiO series, MIL series, ZIF series, HKUST series, PCN series, and MOF-74 series.
[0016] Furthermore, the ionic liquid is selected from one or more of imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium salt ionic liquids, choline ionic liquids, and phosphine salt ionic liquids.
[0017] Preferably, the ionic liquid is one or more of the following: ionic liquids functionalized with carboxyl, sulfonic acid, phosphonic acid, amino, or polyethylene glycol segments.
[0018] Furthermore, the ionic liquid forms a gradient polarity distribution inside the MOF pores. By controlling the length of the cationic alkyl chain, the type of anion, and the type of functional group of the ionic liquid, a gradient change in polarity from the inner wall of the pores to the center of the pores is achieved, so as to optimize the differential recognition and selective adsorption of different lanthanide rare earth metal ions. The ionic liquid forms a multifunctional site synergistic distribution within the MOF pores, including a spatial synergistic arrangement of coordination sites, hydrogen bonding sites, and electrostatic interaction sites.
[0019] Furthermore, the composite material exhibits an adsorption capacity ≥50 mg / g for lanthanide rare earth ions, and Lu... 3+ / Yb 3+The separation coefficient is ≥1.5, the adsorption capacity retention rate is ≥80% after 5 cycles, and it has pore structure stability and low ionic liquid loss rate in aqueous solution systems.
[0020] According to a second aspect of the present invention, a method for preparing an ionic liquid-metal-organic framework composite material having an tunable confined microenvironment as described in any of the foregoing aspects is provided, comprising the following steps: S1. The selected metal-organic framework (MOF) materials are activated to remove residual solvents, water molecules and uncoordinated organic ligands in the pores of the MOFs, so as to obtain activated MOFs with open pore structure. S2. The activated MOFs obtained in step S1 are mixed with the ionic liquid precursor in the reaction solvent. Under closed conditions and constant temperature reaction system, the ionic liquid precursor is constructed in situ within the confined space of the MOF channels to form an ionic liquid. At the same time, the spatial confinement effect of the MOF nanopores is used to stably encapsulate the ionic liquid inside the channels and regulate the interfacial interaction between the ionic liquid and the MOF framework to form an adjustable confined microenvironment. S3. The product obtained in step S2 is washed to remove unbound ionic liquid or ionic liquid precursor. After solid-liquid separation and drying, an ionic liquid-metal-organic framework composite material (IL@MOFs) with an adjustable confined microenvironment is obtained.
[0021] Furthermore, the activation treatment in step S1 is carried out at a temperature of 80-200 °C and for a time of 2-48 hours under vacuum or inert atmosphere. Before activation, the high-boiling-point solvent in the pores of the MOFs is replaced by solvent exchange.
[0022] Furthermore, the ionic liquid precursor mentioned in step S2 includes a cationic precursor, an anionic precursor, or a combination thereof; The reaction temperature for in-situ construction of the ionic liquid precursor within the MOF pores is 20-120℃, and the reaction time is 0.1-24 hours. The mixing method is selected from one or more of the following: impregnation method, ultrasonic-assisted dispersion method, or stirring method; The adjustable confined microenvironment is achieved by controlling one or more factors among the type and amount of ionic liquid precursor, reaction temperature, and reaction time.
[0023] Furthermore, in the in-situ construction process described in step S2, the loading amount and spatial distribution of the ionic liquid in the MOF pores are controlled by adjusting the amount of ionic liquid precursor introduced and / or the reaction conditions, so as to achieve a gradient distribution of polarity and / or functional sites inside the pores. The ionic liquid and the MOF framework interact through an in-situ construction process, forming one or more stable interfacial interactions, including electrostatic interactions, hydrogen bonding interactions, and van der Waals interactions.
[0024] Furthermore, the washing in step S3 uses one or more detergents selected from methanol, ethanol, acetone, and deionized water; the drying is vacuum drying, with a drying temperature of 40-120 ℃ and a drying time of 4-24 hours; in the obtained IL@MOFs composite material, the ionic liquid is stably confined and distributed in the MOFs channels in a non-polymerized and non-coupled form, and the composite material maintains the original crystal structure of MOFs.
[0025] According to a third aspect of the present invention, an application of an ionic liquid-metal-organic framework composite material with an adjustable confined microenvironment as described in any of the above aspects in the adsorption and separation of metal ions is provided, characterized in that: the composite material is used for the selective adsorption, separation and enrichment of lanthanide rare earth metal ions, and / or for the adsorption and separation of transition metal ions.
[0026] Further, the lanthanide rare earth metal ions are selected from at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium. Preferably, the composite material is used for the selective separation of adjacent lanthanide rare earth elements, wherein the adjacent lanthanide rare earth elements include Lu. 3+ / Yb 3+ La 3+ / Ce 3+ Eu 3+ / Gd 3+ At least one of them.
[0027] Furthermore, the composite material is used for the selective recovery and recycling of rare earth metal ions in rare earth ore leaching solutions, rare earth industrial wastewater, high-salt rare earth waste liquid, electronic waste leaching solutions, or leaching solutions of decommissioned permanent magnet materials.
[0028] Furthermore, the adsorption separation process is carried out in a liquid phase system with a pH of 2.0-7.0, an adsorption temperature of 15-60 ℃, and an adsorption time of 0.5-24 hours; the composite material is regenerated by acid desorption after adsorption separation and can be reused.
[0029] Furthermore, the composite material is also used as a multi-active-center catalyst for catalyzing organic conversion reactions, including at least one of oxidation, condensation, esterification, or carbonylation reactions.
[0030] Furthermore: Rare earth ion adsorption capacity ≥50 mg / g; Lu 3+ / Yb3+ Separation coefficient ≥ 1.5; After 5 cycles, the adsorption capacity retention rate is ≥80%; It exhibits pore stability and low ionic liquid loss in aqueous solution systems.
[0031] Here, the key performance indicators of this invention are: adsorption capacity ≥50 mg / g, Lu 3+ / Yb 3+ A separation coefficient ≥1.5 and an adsorption capacity retention rate ≥80% after 5 cycles are of significant technical importance. The ionic radius difference between adjacent lanthanide elements is only about 0.01-0.02 Å, and their chemical behaviors are highly similar, making efficient separation a recognized technical challenge in this field. For lanthanide rare earth separation, increasing the separation coefficient from the current level of 1.10-1.32 to over 1.55, although the numerical increase seems limited, is sufficient to alter the competitive coordination equilibrium of adjacent elements in the confined microenvironment, thereby achieving efficient separation. The adsorption capacity threshold of ≥50 mg / g is also synergistically related to the above mechanism—the selective recognition ability of the confined microenvironment for rare earth ions requires a sufficient density of functional sites. Below this threshold, there are insufficient functional sites within the pores, making it difficult to form an effective gradient polarity distribution and a cooperative coordination network. A retention rate ≥80% after 5 cycles reflects the effectiveness of the non-covalent confinement strategy from a performance perspective. The above values are an objective representation of the overall technical effect of the synergistic effect of the various technical features of the present invention, rather than the result of independent optimization of a single parameter.
[0032] The beneficial effects of this invention are: (1) For the first time, the in-situ construction of non-polymerized / non-coupled confined ionic liquids within the pores of MOFs and the precise construction of tunable confined microenvironments have been achieved: Unlike existing technologies that polymerize ionic liquids into polyionic liquids, covalently graft them onto the MOF framework, or encapsulate them after scaling up the molecular size through coupling reactions, this invention uses ionic liquid precursors to directly form ionic liquids in situ within the confined space of MOF pores, allowing them to exist stably within the pores in a non-polymerized, non-coupled, and non-covalently bonded form, utilizing the confinement effect of the pores. This method fully preserves the molecular conformational freedom, coordination characteristics, and polarity of the ionic liquid monomers, avoiding the problem of active sites being shielded due to polymerization or coupling. Based on this, the present invention proposes for the first time the concept of "tunable confined microenvironment". By controlling the length of the cationic alkyl chain, the type of anion and the types of functional groups of the ionic liquid, a gradient distribution of polarity, electronegativity, coordination ability and hydrophilicity / hydrophobicity inside the pore is achieved, forming a confined microenvironment with spatial heterogeneity. This transforms MOFs from traditional "porous adsorption materials" into "confined microenvironment recognition platforms" with active recognition capabilities.
[0033] (2) Synergistic anchoring of multiple non-covalent interfaces achieves stable confinement and excellent cycling stability of ionic liquids: Unlike the existing technology that relies on a single physical adsorption to load ionic liquids, in this invention, the ionic liquid and the MOF framework are synergistically anchored through one or more non-covalent interface interactions, such as electrostatic interaction, hydrogen bonding, and van der Waals interaction, which effectively inhibits the loss of ionic liquids in the aqueous solution system. After 5 cycles, the adsorption capacity retention rate can reach 84-97%. At the same time, the multiple non-covalent interface interactions do not destroy the crystal structure of MOFs, avoiding the influence of covalent grafting on the integrity of the framework. The uniform confinement distribution of ionic liquids also avoids the problems of pore blockage and mass transfer limitation caused by physical impregnation method, while maintaining the high specific surface area and continuous mass transfer channels of MOFs, and increasing the number of effective functional sites inside the channels.
[0034] (3) Significantly improves the selective recognition and separation ability of lanthanide rare earth ions: Addressing the challenge of insufficient selectivity in traditional adsorption materials due to the extremely small differences in lanthanide ion radii (adjacent elements differ by only about 0.01-0.02 Å) and highly similar chemical properties, this invention achieves differentiated recognition of different rare earth ions through the synergistic coupling of a gradient polar microenvironment and an ionic liquid-MOF framework. The results of the examples show that the composite material of this invention significantly improves the selective recognition of Lu... 3+ and Yb 3+ The adsorption capacities can reach 74-80 mg / g and 52-60 mg / g, respectively, Lu 3+ / Yb 3+ The separation coefficient can reach 1.55-1.68, which is far superior to the 1.10 of unmodified MOFs; in Na + Ca 2+ Mg 2+ K + Despite interference from multiple coexisting ions, the adsorption capacity for rare earth ions (>69 mg / g) is much higher than that for interfering ions (<6 mg / g), demonstrating excellent anti-interference ability and selectivity.
[0035] (4) Achieving synergistic improvement in adsorption capacity, mass transfer performance and cycling stability: The rare earth ion adsorption capacity (>74 mg / g) of the composite material of the present invention is nearly 10 times higher than that of unmodified MOFs (<8 mg / g) and nearly 2 times higher than that of traditional post-impregnation modified materials (<40 mg / g), and adsorption equilibrium can be reached within 15 minutes; after continuous cycling for 5 times, the adsorption capacity retention rate (84-97%) is far better than that of unmodified MOFs (54-58%) and post-impregnation modified materials (65-67%), achieving a synergistic unity of high adsorption capacity, rapid adsorption kinetics and excellent cycling stability.
[0036] (5) The above-mentioned beneficial effects are not simply the sum of the improvements, but are achieved through deep synergy between technical features: ① The existence of ionic liquid in a confined state rather than being polymerized or covalently fixed is the premise for it to form a continuous gradient polarity distribution in the pores; ② During the in-situ formation of the ionic liquid precursor in the confined space of MOFs pores, it fully contacts the inner wall of the pores and gradually establishes multiple non-covalent interface interactions. This "forming-anchoring" synergistic mechanism makes the establishment of interface interactions more sufficient and uniform, which is an effect that is difficult to achieve by the post-impregnation method; ③ The gradient polarity microenvironment and the ionic liquid-MOFs synergistic coupling enable the efficient separation of adjacent lanthanide elements that cannot be effectively distinguished by the MOFs pore size effect or the coordination ability of the ionic liquid alone; ④ The binding energy of multiple non-covalent interface interactions is much higher than that of single physical adsorption, and does not involve the formation and breaking of covalent bonds, so that the material can still exert the molecular recognition ability of free ionic liquid while maintaining excellent cycle stability, thus achieving the unity of stability and functionality. Attached Figure Description
[0037] Figure 1 This is a flowchart of the preparation method of ionic liquid-metal-organic framework composite material (IL@MOFs) with adjustable confined microenvironment according to the technical solution of the present invention. Figure 2 This is a scanning electron microscope image of [BPy][Sal]@NH2-MIL-88B(Fe) prepared in Example 1; Figure 3 This is a graph showing the relationship between the adsorption amount and adsorption time of [BPy][Sal]@NH2-MIL-88B(Fe) prepared in Example 1; Figure 4 This is a selective experimental diagram of [BPy][Sal]@NH2-MIL-88B(Fe) prepared in Example 1; Figure 5 This is a graph showing the relationship between the adsorption capacity of [BPy][Sal]@NH2-MIL-88B(Fe) prepared in Example 1 and the number of cycles. Detailed Implementation
[0038] The embodiments of the present invention are described in detail below. These embodiments are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes. However, the scope of protection of the present invention is not limited to the following embodiments.
[0039] This invention provides an ionic liquid-metal-organic framework (IL@MOFs) composite material with a tunable confined microenvironment, its preparation method, and its applications. By constructing an ionic liquid in situ within the pores of a metal-organic framework (MOF) and utilizing the spatial confinement effect of the MOF nanopores, the ionic liquid is stably distributed within the pores, creating a confined microenvironment with tunable polarity, coordination ability, and hydrophilicity / hydrophobicity. By controlling the composition, loading method, and pore interface structure of the ionic liquid, a stable interfacial interaction is formed between the ionic liquid and the MOF framework, achieving precise control of the internal microenvironment of the material. This enhances the material's recognition ability, adsorption capacity, and selective separation performance for lanthanide rare earth ions.
[0040] This invention achieves highly stable immobilization of ionic liquids within the pores of MOFs through in-situ construction and spatial confinement strategies. For a long time, it has been generally believed in the art that ionic liquids, if not anchored to a support via covalent bonding or polymerization, are highly susceptible to loss in liquid systems. Therefore, existing technologies often employ chemical modification methods such as covalent grafting, polymerization, or coupling to achieve stabilization. This invention overcomes this technical bias. Experiments demonstrate that, under the synergistic effect of spatial confinement and multiple intermolecular interactions within the MOF nanopores, the cyclic stability of the ionic liquid is comparable to that of the covalent grafting method (84-97% retention after 5 cycles, compared to 91-92% for the covalent grafting method), while maintaining higher selective adsorption performance (separation coefficient 1.55-1.68 vs. 1.39 for the covalent grafting method). This indicates that there is no necessary correlation between confined ionic liquids and instability, providing a novel technical approach for this field.
[0041] The present invention first provides an ionic liquid-metal-organic framework composite material (IL@MOFs) with a tunable confined microenvironment. The composite material is composed of metal-organic framework materials (MOFs) and an ionic liquid constructed in situ and confined within the pores of the MOFs. The ionic liquid forms a tunable microenvironment within the pores, including tunable polarity, electronegativity, coordination ability, and hydrophilicity / hydrophobicity, achieving a uniform distribution of functional sites within the pores. The ionic liquid and the MOFs framework form one or more interfacial interactions, including electrostatic interactions, hydrogen bonding interactions, and van der Waals interactions. The introduction of the ionic liquid does not destroy the crystal structure of the MOFs and endows the composite material with a tunable interfacial chemical environment and pore hydrophilicity / hydrophobicity, enabling selective adsorption and separation of lanthanide rare earth metal ions, and exhibiting good stability during recycling.
[0042] In a preferred embodiment, the metal center of the MOFs is selected from one or more of Zn, Cu, Zr, Fe or Cr, and the organic ligand is selected from carboxylic acid, imidazole or pyridine ligands or their derivatives.
[0043] In a preferred embodiment, the MOFs include, but are not limited to, UiO series, MIL series, ZIF series, HKUST series, PCN series, MOF-74 series and their derivative materials.
[0044] In a preferred embodiment, the ionic liquid includes one or more of the following: imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium salt ionic liquids, choline ionic liquids, phosphonate ionic liquids, dicationic ionic liquids, and ionic liquids functionalized with carboxyl, sulfonic acid, phosphonic acid, amino, or polyethylene glycol segments.
[0045] In a preferred embodiment, the ionic liquid is mainly distributed within the MOF pores, and the tunable microenvironment within the MOF pores forms a gradient polarity or multifunctional distribution to optimize the selective adsorption and mass transfer efficiency of different rare earth metal ions. In other words, the ionic liquid forms a gradient distribution or a synergistic distribution of multifunctional sites within the MOF pores, creating a confined microenvironment with spatial heterogeneity within the MOF pores.
[0046] The present invention also provides a method for preparing the IL@MOFs composite material, such as... Figure 1 As shown, it includes: S1. Activate the selected MOFs to remove residual solvent, water molecules and uncoordinated ligands from the pores; S2. Under constant temperature and sealed conditions, the activated MOFs and ionic liquid precursors are mixed evenly in the reaction solvent, so that the ionic liquid is constructed and confined in situ within the MOFs channels to form a tunable microenvironment. S3. Wash, separate and dry to obtain IL@MOFs composite material.
[0047] In a preferred embodiment, the activation temperature in step S1 is 80-200 °C, and the activation time is 2-48 hours, and vacuum or inert atmosphere treatment can be selected; the reaction temperature in step S2 is 20-120 °C, and the reaction time is 0.1-24 hours, and impregnation, ultrasonication or stirring can be used. Ionic liquid precursors include cationic precursors, anionic precursors, or combinations thereof.
[0048] The present invention also provides an IL@MOFs composite material that can be used for the selective adsorption, separation, and enrichment of lanthanide rare earth or transition metal ions, the recovery and recycling of rare earth metal ions, and as a multi-active center material in catalytic reactions to improve conversion rate and selectivity. The application of the above composite material in the adsorption, enrichment, selective separation, and recovery of lanthanide rare earth ions is particularly suitable for the efficient separation of lanthanide elements such as lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium.
[0049] In a preferred embodiment, the rare earth ion adsorption capacity is ≥50 mg / g; Lu 3+ / Yb 3+ Separation coefficient ≥1.5; adsorption capacity retention ≥80% after 5 cycles; exhibits pore stability and low ionic liquid loss in aqueous solution system.
[0050] In a preferred embodiment, the ionic liquid forms a gradient polarity or multifunctional microenvironment inside the pores, and by controlling the type and distribution of the ionic liquid, differentiated recognition and selective adsorption of different rare earth ions can be achieved.
[0051] Therefore, in the technical solution of the present invention, the ionic liquid is formed and stably exists inside the MOFs pores through in-situ construction, and forms one or more interfacial interactions with the MOFs framework, such as electrostatic interaction, hydrogen bonding interaction and van der Waals interaction, forming a confined microenvironment with adjustable polarity, adjustable coordination ability and adjustable hydrophilicity and hydrophobicity within the MOFs pores.
[0052] Example 1
[0053] The selected NH2-MIL-88B(Fe) was activated: the powder was placed in a vacuum tube furnace and activated at 120 °C for 6 h to completely remove the DMF, adsorbed water, and uncoordinated aminoterephthalic acid ligands trapped in the pores. After activation, the powder was cooled to room temperature to obtain a pure NH2-MIL-88B(Fe) substrate material with completely open pores. 1.0 g of NH2-MIL-88B(Fe) was weighed and added to 100 mL of anhydrous ethanol and ultrasonically dispersed for 10 min. 20 mL of 0.05 mol / L 1-butylpyridinium salicylate ([BPy][Sal]) ethanol solution was added to the system, and the mixture was stirred at 40 °C for 12 h. After the reaction, the mixture was centrifuged, washed three times with anhydrous ethanol to remove unbound ionic liquids, and dried under vacuum at 80 °C for 12 h to obtain [BPy][Sal]@NH2-MIL-88B(Fe) composite material A. Its SEM image is shown below. Figure 2 As shown, this material is a uniformly sized polyhedral crystal with clear edges and smooth crystal faces, exhibiting high crystallinity. Individual grains are 100-200 nm in size, belonging to the submicron scale. The particle surfaces are relatively smooth, with no obvious collapse or cracks, indicating complete crystallization and sufficient growth.
[0054] Lu 3+ / Yb 3+ Adsorption experiment: A mixed rare earth solution was prepared by weighing Lu(NO3)3·6H2O and Yb(NO3)3·6H2O respectively. Wherein: Lu 3+The initial concentration was 100 mg / L; Yb 3+ The initial concentration was 100 mg / L. The pH of the solution was adjusted to 4.5 using 0.01 mol / L HNO3 and 0.01 mol / L NaOH. 50 mg of [BPy][Sal]@NH2-MIL-88B(Fe) was weighed and added to 100 mL of mixed rare earth solution. Adsorption was carried out at 25 ℃ and 180 rpm for 12 h with shaking. After adsorption, the mixture was centrifuged, and the supernatant was analyzed by ICP-OES to determine Lu. 3+ and Yb 3+ The relationship between residual concentration, ion adsorption capacity, and time is as follows: Figure 3 As shown, with the extension of adsorption time, the adsorption capacity of both rare earth metal ions showed a pattern of first increasing rapidly, then increasing slowly, and finally stabilizing. In the initial adsorption stage (0-3h), Lu... 3+ and Yb 3+ The adsorption capacity increased rapidly, reaching 58 mg / g and 38 mg / g respectively, indicating the existence of a large number of unoccupied adsorption sites in the material, allowing rare earth ions to diffuse rapidly and bind to these sites. Subsequently, as the adsorption sites were gradually occupied, the adsorption rate slowed down significantly. After approximately 12 hours, the adsorption capacity gradually reached equilibrium, and Lu... 3+ and Yb 3+ The equilibrium adsorption capacities reached 74.30 mg / g and 52.05 mg / g, respectively. 3+ / Yb 3+ The separation coefficient is 1.68.
[0055] Selective experiments: Weigh out NaCl, CaCl2, MgCl2, and KCl. + Ca 2+ Mg 2+ K + A mixed rare earth solution was prepared by mixing Lu(NO3)3·6H2O and Yb(NO3)3·6H2O. The initial concentration of all metal ions was 200 mg·L⁻¹. -1 The sample was reacted with [BPy][Sal]@NH2-MIL-88B(Fe) under the adsorption experimental conditions for 6 h. After adsorption, the sample was centrifuged, and the Na+ content of the supernatant was determined by ICP-OES. + Ca 2+ Mg 2+ K + Lu 3+ and Yb 3+ The remaining concentration, and the results are as follows Figure 4 As shown. Lu 3+ and Yb 3+The maximum adsorption capacities were 70.27 mg / g and 51.21 mg / g, respectively, while Na... + Ca 2+ Mg 2+ K + The adsorption capacities were only 4.12 mg / g, 3.85 mg / g, 5.36 mg / g, and 4.78 mg / g, indicating that the synthesized material had low adsorption capacity for Lu. 3+ and Yb 3+ Its adsorption capacity is much higher than that of Ca. 2+ Mg 2+ Impurity metal ions, etc.
[0056] Recycling experiment: After adsorption equilibrium, the material was centrifuged and then added to 100 mL of 0.10 mol / L HCl solution. The mixture was then shaken and desorbed at 25 °C for 2 h. After desorption, the material was centrifuged again, washed with deionized water until neutral, and then vacuum dried at 80 °C for 12 h. The regenerated material was reused in adsorption experiments. The adsorption-desorption cycle was repeated 5 times, and the results are as follows: Figure 5 As shown. The synthesized material has a positive effect on Lu. 3+ and Yb 3+ The adsorption capacity decreased slightly with increasing cycle number, but remained high overall. After 5 cycles of adsorption-desorption-adsorption, Lu... 3+ and Yb 3+ The adsorption capacities decreased to 65.69 mg / g and 50.43 mg / g, respectively, but still maintained 88.41% and 96.88% of the initial adsorption capacity, indicating that the material has excellent reusability.
[0057] Example 2
[0058] The selected UiO-66 was subjected to vacuum activation treatment: the powder was placed in a vacuum oven and kept at 120 ℃ for 6 h to completely remove DMF, adsorbed water, and uncoordinated terephthalic acid ligands trapped in the pores. After activation, it was naturally cooled to room temperature to obtain a high-purity UiO-66 substrate material with completely open pores. 1.0 g of the prepared UiO-66 powder was weighed and added to 100 mL of anhydrous ethanol and ultrasonically dispersed for 10 min to form a stable suspension. 20 mL of 0.05 mol / L 1-butylpyridinium salicylate ([BPy][Sal]) ethanol solution was added to the system, and the mixture was stirred at 40 ℃ for 12 h to achieve ionic liquid loading modification. After the reaction, the mixture was centrifuged, washed three times with anhydrous ethanol to remove unloaded free ionic liquid, and dried under vacuum at 80 ℃ for 12 h to obtain the [BPy][Sal]@UiO-66 composite material.
[0059] Lu3+ / Yb 3+ Adsorption experiment: Prepare Lu with an initial concentration of 100 mg / L 3+ Yb 3+ A mixed rare earth solution was prepared, and the pH was adjusted to 4.5 using 0.01 mol / L HNO3 and 0.01 mol / L NaOH. 50 mg of the [BPy][Sal]@UiO-66 composite material was accurately weighed and added to 100 mL of the mixed rare earth solution. The solution was placed in a constant-temperature shaking incubator and subjected to constant-temperature shaking at 25 ℃ and 180 rpm for 12 h until adsorption equilibrium was reached. After adsorption, the mixture was centrifuged, and the supernatant was analyzed by ICP-OES to detect Lu. 3+ With Yb 3+ The remaining equilibrium concentration can be calculated to obtain Lu. 3+ and Yb 3+ The maximum adsorption capacities were 79.58 mg / g and 59.78 mg / g, respectively. Calculate Lu 3+ / Yb 3+ The separation coefficient is 1.55.
[0060] Selective experiments: Weigh out NaCl, CaCl2, MgCl2, and KCl. + Ca 2+ Mg 2+ K + A mixed rare earth solution was prepared by mixing Lu(NO3)3·6H2O and Yb(NO3)3·6H2O. The initial concentration of all metal ions was 200 mg·L⁻¹. -1 The [BPy][Sal]@UiO-66 was reacted with the adsorption experimental conditions for 6 h. After adsorption, the mixture was centrifuged, and the supernatant was analyzed by ICP-OES for Na. + Ca 2+ Mg 2+ K + Lu 3+ and Yb 3+ Remaining concentration, Na + Ca 2+ Mg 2+ K + Lu 3+ and Yb 3+ The maximum adsorption capacities were 3.34 mg / g, 4.22 mg / g, 5.67 mg / g, 5.38 mg / g, 74.69 mg / g, and 57.85 mg / g, respectively.
[0061] Recycling experiment: The adsorbed material was collected by centrifugation and added to 100 mL of 0.10 mol / L HCl desorption solution. Desorption was carried out at 25 °C with shaking for 2 h. After desorption, the material was separated by centrifugation, and repeatedly washed with deionized water until the washing solution was neutral. Regeneration was completed by vacuum drying at 80 °C for 12 h. The regenerated material was subjected to repeated adsorption-desorption cycle experiments. After 5 consecutive cycles, the material Lu... 3+ and Yb 3 + The adsorption capacity retention rates can reach 86.74% and 95.13%, respectively, and it has excellent reusability.
[0062] Example 3
[0063] The selected NH2-MIL-88B(Fe) was activated: the powder was placed in a vacuum tube furnace and activated at 120 ℃ for 6 h to completely remove the DMF, adsorbed water, and uncoordinated aminoterephthalic acid ligands trapped in the pores. After activation, the powder was cooled to room temperature to obtain a pure NH2-MIL-88B(Fe) substrate material with completely open pores. 1.0 g of NH2-MIL-88B(Fe) powder was weighed and dispersed in 100 mL of anhydrous ethanol, and ultrasonically dispersed for 10 min to obtain a uniform suspension. Tetrabutylammonium bromide (TBTA) was selected as a modifier, and 20 mL of 0.05 mol / L tetrabutylammonium bromide ethanol solution was prepared. This solution was slowly added dropwise to the above MOF suspension, and the mixture was stirred at 40 ℃ for 12 h to complete the loading modification of the quaternary ammonium salt ionic liquid. After the reaction was completed, the product was separated by centrifugation and washed three times with anhydrous ethanol to completely remove unbound free quaternary ammonium salt ionic liquid. The product was then dried under vacuum at 80 °C for 12 h to obtain TBAB@NH2-MIL-88B(Fe) composite material C.
[0064] Lu 3+ / Yb 3+ Adsorption experiment: Formulating Lu 3+ Yb 3+ A mixed rare earth solution with an initial concentration of 100 mg / L was prepared, and the pH was adjusted to 4.5. 50 mg of TBAB@NH2-MIL-88B(Fe) composite material was added to 100 mL of the mixed rare earth solution, and adsorption was carried out at 25 ℃ and 180 rpm for 12 h until equilibrium was reached. After centrifugation, the ion concentration of the supernatant was determined by ICP-OES, and the Lu was calculated. 3+ Yb 3+ The maximum adsorption capacities were 74.52 mg / g and 53.65 mg / g, respectively. Calculate Lu 3+ / Yb 3+ The separation coefficient is 1.62.
[0065] Selective experiments: Weigh out NaCl, CaCl2, MgCl2, and KCl. + Ca 2+ Mg 2+ K + A mixed rare earth solution was prepared by mixing Lu(NO3)3·6H2O and Yb(NO3)3·6H2O. The initial concentration of all metal ions was 200 mg·L⁻¹. -1 The sample was reacted with TBAB@NH2-MIL-88B(Fe) under the adsorption experimental conditions for 6 h. After adsorption, the sample was centrifuged, and the supernatant was analyzed by ICP-OES for Na. + Ca 2+ Mg 2+ K + Lu 3+ and Yb 3+ Remaining concentration, Na + Ca 2+ Mg 2+ K + Lu 3+ and Yb 3+ The maximum adsorption capacities were 4.95 mg / g, 3.51 mg / g, 4.67 mg / g, 3.98 mg / g, 69.22 mg / g, and 51.14 mg / g, respectively.
[0066] Recycling experiment: In the cyclic regeneration experiment, the adsorption-saturated composite material was collected by centrifugation and placed in 100 mL of 0.10 mol / L HCl solution for desorption by shaking at 25 °C for 2 h. After desorption, it was washed with water until neutral and then vacuum dried to complete regeneration. Five consecutive adsorption-desorption cycles were performed to determine the Lu' content of the quaternary ammonium salt modified composite material. 3+ and Yb 3+ The adsorption capacity retention rates can reach 89.74% and 95.87%, and it has excellent reusability.
[0067] Comparative Example 1 2.70 g of FeCl3·6H2O and 1.81 g of 2-aminoterephthalic acid were weighed and dispersed together in 100 mL of DMF solvent. The mixture was ultrasonically dispersed for 15 min and magnetically stirred for 30 min to obtain a homogeneous precursor solution. The precursor was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at a constant temperature of 110 ℃ for 24 h. After the reaction was completed, the mixture was naturally cooled to room temperature, and the solid product was collected by centrifugation. The product was washed three times alternately with DMF and anhydrous ethanol to remove unreacted organic ligands and residual solvent. The product was then vacuum dried at 80 ℃ for 12 h to obtain unmodified pure NH2-MIL-88B(Fe) porous material D.
[0068] Lu 3+ / Yb 3+ Adsorption experiment: Formulating Lu 3+ Yb 3+ A binary mixed rare earth solution with an initial concentration of 100 mg / L was prepared using 0.01 mol / L HNO3. 3 The pH of the system was adjusted to 4.5 with 0.01 mol / L NaOH. 50 mg of pure NH₂-MIL-88B(Fe) powder was weighed and added to 100 mL of mixed rare earth solution. The mixture was incubated at 25 ℃ and 180 rpm for 12 h until adsorption equilibrium was reached. After adsorption, the supernatant was collected by centrifugation, and the residual Lu in the solution was determined using ICP-OES. 3+ Yb 3+ Equilibrium concentration. Test results show that pure NH2-MIL-88B(Fe) has an effect on Lu. 3+ Yb 3+ The adsorption capacities were 7.24 mg / g and 6.60 mg / g, respectively. Calculate their Lu... 3+ / Yb 3+ The separation coefficient is only 1.10.
[0069] Selective experiments: Weigh out NaCl, CaCl2, MgCl2, and KCl. + Ca 2+ Mg 2+ K + A mixed rare earth solution was prepared by mixing Lu(NO3)3·6H2O and Yb(NO3)3·6H2O. The initial concentration of all metal ions was 200 mg·L⁻¹. -1 The sample was reacted with NH2-MIL-88B(Fe) under the adsorption experimental conditions for 6 h. After adsorption, the sample was centrifuged, and the supernatant was analyzed by ICP-OES to determine the Na+ content. + Ca 2+ Mg 2 + K + Lu 3+ and Yb 3+ Remaining concentration, Na + Ca 2+ Mg 2+ K + Lu 3+ and Yb 3+ The maximum adsorption capacities were 2.56 mg / g, 2.96 mg / g, 1.98 mg / g, 2.67 mg / g, 6.97 mg / g, and 6.55 mg / g, respectively.
[0070] Recycling experiment: The adsorption-saturated pure NH₂-MIL-88B(Fe) was centrifuged and added to 100 mL of 0.10 mol / L dilute HCl solution for desorption by shaking at 25 °C for 2 h. After desorption, the solid was collected by centrifugation, washed repeatedly with deionized water until neutral, and then dried under vacuum at 80 °C to complete regeneration. After five consecutive adsorption-desorption cycles, Lu 3+ and Yb 3+ The adsorption capacity retention rates were only 57.74% and 54.31%, respectively, indicating poor cycling stability.
[0071] Comparative Example 2 Weigh 1.0 g of dried and activated NH2-MIL-88B(Fe) powder and disperse it uniformly in 100 mL of anhydrous ethanol. Sonicate for 10 min to form a homogeneous suspension. Measure 20 mL of 0.05 mol / L 1-butylpyridinium salicylate ([BPy][Sal]) ethanol solution and slowly add it dropwise to the MOF suspension. Static impregnation at room temperature for 24 h in a sealed environment. After impregnation, centrifuge, wash three times with anhydrous ethanol to remove physically adsorbed free ionic liquids from the surface, and vacuum dry at 80 ℃ for 12 h to obtain the post-impregnation modified [BPy][Sal]@NH2-MIL-88B(Fe) composite material E.
[0072] Lu 3+ / Yb 3+ Adsorption experiment: Prepare 100 mg / L Lu under the same experimental conditions. 3+ / Yb 3+ The mixed solution was adjusted to pH 4.5, and 50 mg of the impregnation-modified material was weighed and subjected to isothermal shaking adsorption for 12 h. ICP-OES test results showed that the material exhibited good adsorption of Lu... 3+ Yb 3+ The adsorption capacities were 39.58 mg / g and 31.50 mg / g, respectively. Calculate their Lu... 3+ / Yb 3+ The separation coefficient is 1.32.
[0073] Selective experiments: Weigh out NaCl, CaCl2, MgCl2, and KCl. + Ca 2+ Mg 2+ K + A mixed rare earth solution was prepared by mixing Lu(NO3)3·6H2O and Yb(NO3)3·6H2O. The initial concentration of all metal ions was 200 mg·L⁻¹. -1The [BPy][Sal]@NH2-MIL-88B(Fe) modified by the post-impregnation method was reacted under the adsorption experimental conditions for 6 h. After adsorption, the mixture was centrifuged, and the Na+ content of the supernatant was determined by ICP-OES. + Ca 2+ Mg 2+ K + Lu 3+ and Yb 3+ Remaining concentration, Na + Ca 2+ Mg 2+ K + Lu 3+ and Yb 3+ The maximum adsorption capacities were 3.06 mg / g, 4.51 mg / g, 3.65 mg / g, 4.74 mg / g, 37.66 mg / g, and 29.97 mg / g, respectively.
[0074] Recycling experiment: The adsorption-saturated post-impregnation modified [BPy][Sal]@NH2-MIL-88B(Fe) was centrifuged and added to 100 mL of 0.10 mol / L dilute HCl solution. Desorption was carried out at 25 °C with shaking for 2 h. After desorption, the solid was collected by centrifugation, washed repeatedly with deionized water until neutral, and regenerated by vacuum drying at 80 °C. After five consecutive adsorption-desorption cycles, Lu... 3+ and Yb 3+ The adsorption capacity retention rates were only 67.20% and 65.48%, indicating poor cycling stability.
[0075] Comparative Example 3 1.0 g of dried and activated NH2-MIL-88B(Fe) powder was weighed and uniformly dispersed in 50 mL of anhydrous DMF. The mixture was sonicated for 10 min to form a homogeneous suspension. 0.5 g of 1-carboxypropyl-3-methylimidazolium chloride ([HOOC(CH2)3mim]Cl) was weighed and dissolved in 10 mL of anhydrous DMF. This solution was slowly added dropwise to the above MOF suspension. The mixture was stirred at 110 °C for 24 h to allow the carboxyl-functionalized ionic liquid to be chemically grafted onto the MOF framework through coordination between the carboxyl groups and the Fe metal clusters. After the reaction, the mixture was centrifuged and washed three times each with DMF and anhydrous ethanol to remove unreacted ionic liquid. The mixture was then vacuum dried at 80 °C for 12 h to obtain the covalently grafted modified [HOOC(CH2)3mim]Cl@NH2-MIL-88B(Fe) composite material F.
[0076] Lu 3+ / Yb 3+ Adsorption experiment: Lu was prepared under the same conditions as in Example 1. 3+ Yb 3+ A mixed rare earth solution (pH 4.5) with an initial concentration of 100 mg / L was prepared. 50 mg of composite material F was added to 100 mL of the mixed rare earth solution, and adsorption was carried out at 25 ℃ and 180 rpm for 12 h with shaking. After centrifugation, the ion concentration of the supernatant was determined by ICP-OES, and the Lu was calculated. 3+ Yb 3+ The maximum adsorption capacities were 48.67 mg / g and 37.52 mg / g, respectively, for Lu. 3+ / Yb 3+ The separation coefficient is 1.39.
[0077] Selective experiments: Selectivity experiments were conducted under the same conditions as in Example 1, Na + Ca 2+ Mg 2+ K + Lu 3+ and Yb 3+ The maximum adsorption capacities were 3.28 mg / g, 4.01 mg / g, 3.87 mg / g, 4.22 mg / g, 45.93 mg / g, and 35.67 mg / g, respectively.
[0078] Recycling experiment: A cyclic regeneration experiment was conducted under the same conditions as in Example 1. After five consecutive cycles, Lu... 3+ and Yb 3+ The adsorption capacity retention rates were 91.42% and 92.17%, respectively.
[0079] Comparative Example 4 Rare earth ion adsorption experiments were performed directly using the free ionic liquid [BPy][Sal] without introducing any MOF materials. Lu was prepared... 3+ Yb 3+ 100 mL of a mixed rare earth solution with an initial concentration of 100 mg / L was prepared, and the pH was adjusted to 4.5. An equivalent amount of ionic liquid [BPy][Sal] (approximately 1.0 mmol of the total ionic liquid in 20 mL of 0.05 mol / L [BPy][Sal] ethanol solution) was added to the solution, and the mixture was shaken and adsorbed at 25 °C and 180 rpm for 12 h. After adsorption, the mixture was centrifuged, and the supernatant G was used to determine the Lu content using ICP-OES. 3+ and Yb 3+ Remaining concentration.
[0080] Test results show that the free state [BPy][Sal] affects Lu 3+and Yb 3+ The adsorption capacities were 14.52 mg / g and 13.87 mg / g, respectively, for Lu. 3+ / Yb 3+ The separation coefficient was 1.05, indicating that the adsorption amounts of the two ions were almost identical, suggesting that the free ionic liquid has virtually no selective recognition ability for adjacent lanthanide rare earth ions. Furthermore, due to the high dispersion of the free ionic liquid in solution, effective recovery cannot be achieved through centrifugation or filtration.
[0081] Comparative Example 5 The same MOFs material and ionic liquid as in Example 1 were used, but the method of introducing the ionic liquid was changed: 1.0 g of activated NH2-MIL-88B(Fe) powder was added to 100 mL of anhydrous ethanol and ultrasonically dispersed for 10 min to form a suspension. Then, 20 mL of 0.05 mol / L [BPy][Sal] ethanol solution was added at once and stirred at room temperature for 1 min. The mixture was then immediately centrifuged and separated. Without a 12 h isothermal reaction, the mixture was washed three times with anhydrous ethanol and vacuum dried at 80 ℃ for 12 h to obtain composite material H, in which the ionic liquid was mainly distributed on the outer surface and pore area of the MOFs.
[0082] Lu 3+ / Yb 3+ Adsorption experiment: Lu was prepared under the same conditions as in Example 1. 3+ Yb 3+ A mixed rare earth solution (pH 4.5) with an initial concentration of 100 mg / L was prepared. 50 mg of composite material H was added to 100 mL of the mixed rare earth solution, and adsorption was carried out at 25 ℃ and 180 rpm for 12 h with shaking. After centrifugation, the ion concentration of the supernatant was determined by ICP-OES, and the Lu was calculated. 3+ Yb 3+ The maximum adsorption capacities were 22.35 mg / g and 20.18 mg / g, respectively, for Lu. 3+ / Yb 3+ The separation coefficient is 1.12.
[0083] Selective experiments: Selectivity experiments were conducted under the same conditions as in Example 1, Na + Ca 2+ Mg 2+ K + Lu 3+ and Yb 3+ The maximum adsorption capacities were 2.87 mg / g, 3.12 mg / g, 2.56 mg / g, 3.01 mg / g, 20.68 mg / g, and 18.93 mg / g, respectively.
[0084] Recycling experiment: A cyclic regeneration experiment was conducted under the same conditions as in Example 1. After five consecutive cycles, Lu... 3+ and Yb 3+ The adsorption capacity retention rates were 65.32% and 63.78%, respectively.
[0085] As shown in Comparative Example 5, even when using the exact same MOFs material and ionic liquid as in Example 1, if the isothermal reaction during the in-situ construction process is not performed to allow the ionic liquid precursor to fully migrate, distribute, and stably encapsulate within the confined space of the MOFs pores, but only rapid mixing is used to ensure that the ionic liquid is mainly distributed on the outer surface and pore area of the MOFs, the resulting material will have a lower Lu's efficiency. 3+ and Yb 3+ The separation coefficient of the modified MOFs was only 1.12, which is basically equivalent to that of the unmodified MOFs (Comparative Example 1, separation coefficient 1.10), and much lower than that of Example 1 (1.68). Furthermore, the cycling stability was significantly worse than that of Example 1. This indicates that the technical effect of the present invention does not stem from a simple combination of ionic liquids and MOFs, but rather relies on the effective gradient distribution of the ionic liquid within the MOF pores and the synergistic establishment of multiple non-covalent interface interactions between the ionic liquid and the MOF framework. Without confined encapsulation and interface control during the in-situ construction process, even with the same chemical composition, an effective tunable confined microenvironment cannot be formed, thus preventing the attainment of highly selective rare earth separation performance.
[0086] Table 1 - Adsorption, separation, and recycling performance of the materials synthesized in the Examples and Comparative Examples for rare earth ions.
[0087] From comparative examples 1-5, we can see that: Comparative Example 1 shows that the unmodified MOFs have extremely low adsorption capacity and selectivity for lanthanide rare earth ions (Lu / Yb separation coefficient is only 1.10), and have almost no selective separation ability. This indicates that it is difficult to effectively distinguish adjacent lanthanide elements by relying solely on the pore size effect and limited active sites of MOFs.
[0088] Comparative Example 2 shows that although the post-impregnation method can introduce ionic liquid to improve the separation selectivity to a certain extent (Lu / Yb separation coefficient is 1.32), the performance improvement is limited due to the uneven distribution of ionic liquid in the pores and its easy loss, and the cycle stability is poor.
[0089] Comparative Example 3 shows that although the existing covalent grafting method can achieve good cycling stability (retention rate >91% after 5 cycles), the conformational freedom and spatial orientation of the ionic liquid are restricted after it is covalently anchored to the MOF framework, making it difficult to fully utilize the molecular recognition ability of the ionic liquid for rare earth ions. Its Lu / Yb separation coefficient (1.39) is significantly lower than that of Example 1 (1.68), and Lu 3+ The adsorption capacity (48.67 mg / g) was also much lower than that in Example 1 (74.30 mg / g).
[0090] Comparative Example 4 shows that free-state ionic liquids have an effect on Lu 3+ and Yb 3+ The adsorption amounts were almost identical (separation coefficient was only 1.05), indicating that the confinement effect of MOF channels and the synergistic effect of the framework are necessary conditions for achieving high selective separation, and the coordination ability of ionic liquids alone is insufficient to distinguish adjacent lanthanide elements.
[0091] Comparative Example 5 shows that even when using the exact same MOFs material and ionic liquid as in Example 1, if the isothermal reaction step in the in-situ construction process is not performed to allow the ionic liquid to fully migrate, distribute, and establish multiple interfacial interactions within the pores, but only through rapid mixing to ensure the ionic liquid is mainly distributed on the outer surface and pore area of the MOFs, the Lu / Yb separation coefficient of the resulting material (1.12) is basically equivalent to that of the unmodified MOFs, but much lower than that of Example 1 (1.68), and the cycle stability is also significantly deteriorated. This further proves that the technical effect of the present invention depends on the effective gradient distribution of the ionic liquid inside the MOFs pores and the synergistic establishment of multiple non-covalent interfacial interactions between the ionic liquid and the MOFs framework, rather than a simple combination of ionic liquid and MOFs.
[0092] The above comparison results fully demonstrate that the technical solution of the present invention, which integrates "in-situ construction of non-polymerized free ionic liquids + synergistic anchoring of multiple non-covalent interfaces + adjustable confined microenvironment", is the key to obtaining high-selectivity rare earth separation performance, and the above technical effects cannot be reasonably expected through the existing technical path shown in the comparative example.
[0093] In summary, this invention provides an ionic liquid-metal-organic framework composite material IL@MOFs with an adjustable confined microenvironment. By constructing the ionic liquid in situ within the pores of MOFs and utilizing the spatial confinement effect to achieve its stable distribution, the adsorption capacity and selectivity of the material for lanthanide rare earth ions are significantly improved.
[0094] While several embodiments of the present invention have been provided herein, those skilled in the art should understand that changes can be made to the embodiments without departing from the spirit of the invention. The above embodiments are merely exemplary and should not be construed as limiting the scope of the invention.
Claims
1. An ionic liquid-metal-organic framework composite material with a tunable confined microenvironment, characterized in that: The composite material comprises metal-organic framework materials (MOFs) and an ionic liquid confined within the pores of the MOFs. The ionic liquid is constructed in situ within the channels of MOFs in a confined state that is non-polymerized, non-coupled, and non-covalently grafted. It exists stably through the confinement effect of the channels, and the introduction of the ionic liquid does not destroy the crystal structure of MOFs. The ionic liquid forms a tunable confined microenvironment inside the MOF pores, and the tunable confined microenvironment has spatial heterogeneity. The composite material exhibits selective adsorption and separation properties for lanthanide rare earth metal ions, and maintains structural stability and adsorption performance during recycling.
2. The composite material according to claim 1, characterized in that: The ionic liquid forms one or more interfacial interactions with the MOF framework, including electrostatic interactions, hydrogen bonding interactions, and van der Waals interactions. The adjustable confined microenvironment is achieved by regulating the composition of the ionic liquid, the type of functional groups, and their spatial distribution within the pores to synergistically regulate the polarity, electronegativity, coordination ability, and hydrophilicity / hydrophobicity within the pores; the ionic liquid exhibits a gradient polarity distribution or a synergistic distribution of multifunctional sites within the pores.
3. The composite material according to claim 1, characterized in that: The metal center of the MOFs is selected from one or more of Zn, Cu, Zr, Fe, Al, and Cr, and the organic ligand is selected from one or more of carboxylic acid ligands, imidazole ligands, pyridine ligands and their derivatives; wherein the MOFs are selected from one or more of the UiO series, MIL series, ZIF series, HKUST series, PCN series, and MOF-74 series. The ionic liquid is selected from one or more of imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium salt ionic liquids, choline ionic liquids, phosphine salt ionic liquids and their functionalized derivatives; wherein, the ionic liquid achieves a gradient change in polarity and a gradient distribution of coordination ability from the inner wall of the pore to the center region of the pore by regulating the length of the cation alkyl chain, the type of anion and the type of functional group.
4. The composite material according to claim 1, characterized in that: The composite material has an adsorption capacity for lanthanide rare earth ions ≥ 50 mg / g, Lu 3+ / Yb 3+ The separation coefficient is ≥1.5, the adsorption capacity retention rate is ≥80% after 5 cycles, and it has pore structure stability and low ionic liquid loss rate in aqueous solution systems.
5. A method for preparing an ionic liquid-metal-organic framework composite material with an tunable confined microenvironment as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. The selected metal-organic framework materials (MOFs) are activated to remove residual solvents, water molecules and uncoordinated organic ligands from the pores of the MOFs, thereby obtaining activated MOFs with open pore structures. S2. The activated MOFs obtained in step S1 are mixed with the ionic liquid precursor in the reaction solvent. Under closed conditions and constant temperature reaction system, the ionic liquid precursor is constructed in situ within the confined space of the MOF channels to form an ionic liquid. At the same time, the spatial confinement effect of the MOF nanopores is used to stably encapsulate the ionic liquid inside the channels and regulate the interfacial interaction between the ionic liquid and the MOF framework to form an adjustable confined microenvironment. S3. The product obtained in step S2 is washed to remove unbound ionic liquid or ionic liquid precursor. After solid-liquid separation and drying, ionic liquid-metal-organic framework composite material IL@MOFs with tunable confined microenvironment is obtained.
6. The preparation method according to claim 5, characterized in that: The activation treatment in step S1 is carried out at a temperature of 80-200 ℃ and for a time of 2-48 hours, under vacuum or inert atmosphere. The ionic liquid precursor in step S2 includes a cationic precursor, an anionic precursor, or a combination thereof. The in-situ construction reaction temperature is 20-120 °C, and the reaction time is 0.1-24 hours. The mixing method is selected from one or more of the following: impregnation method, ultrasonic-assisted dispersion method, or stirring method.
7. The preparation method according to claim 5, characterized in that: In the in-situ construction process described in step S2, the loading amount and spatial distribution of ionic liquid in MOFs channels are controlled by adjusting one or more factors among the type and amount of ionic liquid precursor, reaction temperature and reaction time, so as to achieve the gradient distribution of polarity and functional sites inside the channels. The ionic liquid and the MOF framework interact through an in-situ construction process, forming one or more stable interfacial interactions, including electrostatic interactions, hydrogen bonding interactions, and van der Waals interactions.
8. The preparation method according to claim 5, characterized in that: The washing in step S3 uses one or more detergents selected from methanol, ethanol, acetone, and deionized water; the drying is vacuum drying, with a drying temperature of 40-120 ℃ and a drying time of 4-24 hours. In the obtained IL@MOFs composite material, the ionic liquid is stably confined and distributed in a non-polymerized and non-coupled free state within the MOFs channels, and the composite material maintains the original crystal structure of MOFs.
9. The application of an ionic liquid-metal-organic framework composite material with an adjustable confined microenvironment as described in any one of claims 1-4 in the adsorption and separation of lanthanide rare earth metal ions, characterized in that: The composite material is used for the selective adsorption, separation and enrichment of lanthanide rare earth metal ions, wherein the lanthanide rare earth metal ions are selected from at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium. The composite material is also used for the selective separation of adjacent lanthanide rare earth elements, including Lu. 3+ / Yb 3+ La 3+ / Ce 3+ Eu 3+ / Gd 3+ At least one of them.
10. The application according to claim 9, characterized in that: The composite material is used for the selective recovery and recycling of rare earth metal ions in rare earth ore leaching solutions, rare earth industrial wastewater, high-salt rare earth waste liquid, electronic waste leaching solutions, or decommissioned permanent magnet material leaching solutions. The adsorption separation process is carried out in a liquid phase system with a pH of 2.0-7.0, an adsorption temperature of 15-60℃, and an adsorption time of 0.5-24 hours. The composite material is regenerated by acid desorption after adsorption and separation, and can be reused.